Tax Avoidance: The Scope and Effect of Section 140 of the Income Tax Act 1967 - Teo, Keang Sood (Journal of Malaysian and Comparative Law, 2019)
There is an important distinction between tax evasion and tax avoidance. Tax evasion refers to all activities deliberately undertaken by a tax-payer to free himself from tax which the law charged upon his income, for example, the falsification of return, books and accounts or the suppression of some material facts. These schemes are illegal and are subject to very heavy and severe penalties. To constitute evasion there must be an intention to deceive.